Perhitungan Biaya Satuan Pada Tindakan Intensive Unit Care di Rumah Sakit X di Jember Melalui Metode Activity Based Costing (ABC) - Witcahyo, Eri (UI Scholars Hub, 2019)
Hospital X in Jember is one of the government hospitals with C type status. In National Health Insurance (JKN) era, the payment scheme in hospital by using the INA CBG’s tariff package. Hospital could have profit or even loss, therefore health services effiency was needed. The objective of study was to identify service product and calculate of service product unit cost at Intensive Care Unit (ICU) in Hospital X in Jember. The type of this research was observational descriptive with cross sectional approach. The unit of analysis was ICU at Hospital X in Jember. The unit cost calculation method is using Acivity Based Costing. The result of the study shown that there were 21 service products that have various unit costs. The highest was Rp. 176,954, - (cardiac pulmonary resuscitation), the lowest was Rp. 27,061,- (intravena injection) and an average of Rp. 75,959, -. The conclusion shown that unit cost was strongly influenced by the resources used, the more efficient resources used for effective services, the smaller unit cost could get. Compared to INA CBG’s package tariff it will be able to create profit surplus for hospital.